Authority, legitimacy and social reality in the film Kynódontas, by Giorgos Lanthimos - García-Dussán, Éder (Romanica Olomucensia, 2014)
This article shows the analysis and interpretation of the structures and functions of the speech of legitimization reflected in the film Kynodontas (Dogtooth), produced in October 2009 by Georgios Lamthinos. To get to this proposal, the qualities and social implications of discursive acts of the legitimation are described and they are evident in the film with the help of an analytical linguistic model, primarily based on the positions of Luisa Martín Rojo, Teun van Dijk, and Theo van Leeuwen, which establishes the research and review of items in the grammatical, semantic, pragmatic levels. After the comprehensive work, it is proved the presence of an authority, the Father, who pushes the behavioral control of his social group through an own idiolect - that could be called strategic-emergent discourse - and that it becomes the essential tool of the current dramaturgy of domination, used in societies that impose tyrannical systems.
Keywords: legitimation discurse; social reality; authority; control; cinematographic text.